2018
DOI: 10.1007/s40264-018-0637-3
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-hospital Before–After Observational Study Using a Point-Prevalence Approach with an Infusion Safety Intervention Bundle to Reduce Intravenous Medication Administration Errors

Abstract: Registered at ClinicalTrials.gov, identifier: NCT02359734.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(64 citation statements)
references
References 21 publications
0
63
0
Order By: Relevance
“…The introduction of smart infusion devices, standards, or the interventions introduced by Schnock et al [9] are not instant solutions to the problem of intravenous infusion administration errors, and may be better considered as ‘probes’ to better understand what does and does not work in a particular context, and what might work well in the future [34]. Thus, the question is not whether smart infusion devices are safer than traditional infusion devices, whether particular standards are optimal, or whether a particular intervention will universally lead to safer practices, but whether particular configurations of technology, procedures, practices and people are likely to enhance or diminish safety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of smart infusion devices, standards, or the interventions introduced by Schnock et al [9] are not instant solutions to the problem of intravenous infusion administration errors, and may be better considered as ‘probes’ to better understand what does and does not work in a particular context, and what might work well in the future [34]. Thus, the question is not whether smart infusion devices are safer than traditional infusion devices, whether particular standards are optimal, or whether a particular intervention will universally lead to safer practices, but whether particular configurations of technology, procedures, practices and people are likely to enhance or diminish safety.…”
Section: Discussionmentioning
confidence: 99%
“…Reporting on smart infusion device implementation in one hospital, Keohane et al [8] highlight the importance of creating a culture in which staff value their own competence and patient safety, and in which technology is easy to use correctly and implementation is viewed as a process of continual upgrade. Schnock et al [9] introduced an infusion safety intervention bundle in nine United States (US) hospitals comprising eight interventions to address areas of medication labelling and tube tagging, administration of unauthorised medications and smart infusion device use. Different components of the bundle were adopted and adapted by different hospitals, and local contextual factors influenced uptake and effectiveness of the interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Our current view of IV medication administration as a complex domain is supported by recent work by Schnock et al, 87 who introduced an infusion safety intervention bundle into their participating hospitals. This comprised eight interventions to address areas of IV labelling and tube tagging (e.g.…”
Section: Rethinking Intravenous Infusion Administration As a Complex mentioning
confidence: 83%
“…Our data do not support this view, and neither does the most recent published study from the USA. 87 This might have been true in the days when IV infusion administrations were delivered via gravity feed, but we have searched for evidence that errors in IV infusion administration are resulting in patient harm and have found little. In practice, we identified only one error likely to lead to patient harm out of 2008 observations, and Schnock et al 7,87 have reported similarly small numbers.…”
Section: Is There a Problem To Be Addressed?mentioning
confidence: 99%
See 1 more Smart Citation